Nutritional value of triticale for growing swine - Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred thirty-five pigs averaging 57 pounds were used to determine the feeding value of triticale and the influence of physical form (meal or pellet) on the performance of growing pigs. Triticale replaced 20, 40, 60, 80, or 100% of the milo in a 16.5% crude protein, milo-soybean diet. Level of triticale had no significant effect on feed intake, daily gain, or feed:gain ratio. Pigs fed triticale supplemented with soybean meal (isonitrogenous with control) and the pigs fed triticale supplemented with 0.2% L-lysine gained significantly (P <.05) slower than pigs fed the control diet. Physical form (meal or pellet) had no significant effect on feed intake, daily gain, or feed:gain ratio. The results indicate that triticale can be substituted on a weight basis in diets for growing pigs but not on a protein basis.
Swine Industry Day 1972 is known as Swine Day 1972
Keywords: Swine; Nutritional value; Triticale; Growing pigs; Milo; Feed/gain ratio